Methods of casting of composite aluminium alloys with graphite particles - V. V. Ovchinnikov; A. T. Volochko; A. P. Laskovnev; Zh. E. Makarova (Литьë и металлургия)
The article describes the basic methods of casting of antifriction aluminium-graphite alloys and their peculiarities.